Acta Nova Humanistica: the New Academic Journal of New Bulgarian University - Board, Editorial (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2024)
Acta Nova Humanistica is the title of New Bulgarian University’s latest academic journal, dedicated to the humanities. Its mission, bolstered by open access and English as its working language, is to open new horizons for both established and emerging scholars, extending their reach to a broader academic audience beyond Bulgaria. As the title suggests, the journal deliberately avoids narrow specialisation, striving instead to support and encourage interdisciplinary approaches to the issues in focus.